Painful considerations in exercise-management for rotator cuff related shoulder pain: a scoping review on pain-related prescription parameters - Kaspar Raulline Ullern; Magnus Richardsen; Ishanka Weerasekara; Bård Erik Bogen (BMC Musculoskeletal Disorders)
Abstract Background Resistance exercise is recommended as the first line of treatment for rotator cuff related shoulder pain (RCRSP), but with conflicting evidence supporting the superiority of specific prescription parameters. Particularly, the role of pain-related prescription parameters remains poorly understood, despite their wide clinical application and potential impact on treatment outcomes. This review aims to investigate how pain-related prescription parameters, such as pain allowance and intensity limits, are reported, described, and applied in clinical trials assessing resistance exercise interventions for RCRSP. Methods Guided by PRISMA-ScR, this scoping review followed a comprehensive and systematic search in MEDLINE (Ovid), MEDLINE (EMBASE), Central (Cochrane), PEDro and CINAHL (EBSCO). Two authors independently performed title and abstract screening, and full text screening on eligible records. Randomized clinical trials (RCTs) published in English between 2018 and 2023, applying resistance exercise for RCRSP were included. Both quantitative and qualitative approaches to data analysis were conducted. Results The literature search identified 7500 records, of which 4588 titles and abstracts were screened after duplicate removal. Altogether, 304 full texts were screened leaving a total of 86 records in the final analysis. Fifty-eight (67%) studies did not mention the use of any pain-related prescription parameters, resulting in data extraction from the 28 remaining studies. Applied parameters were widely heterogenic, but three categories of pain allowance styles were identified and categorized into “yes”, “no” or “ambiguous”. These categories were commonly guided by specific Numerical Rating Scale (NRS)/Visual Analog Scale (VAS) limits or individual pain tolerance, used for pain monitoring and exercise progression. Citations and/or justifications for the chosen pain-related prescription parameters were reported by 10 (36%) studies, in which 5 main themes for justifications, and 3 key papers for the citations were identified. Conclusion This review reveals substantial reporting deficiencies regarding pain-related prescription parameters in RCTs addressing RCRSP with resistance exercise. The identified parameters varied widely, reflecting a lack of consensus and evidence-based guidance in the literature and in a clinical setting. To advance our understanding on the role of pain-related prescription parameters, more consistent reporting of these parameters in future research is warranted. Trial registration Published on the Open Science Framework 28.02.24: osf.io/a52kn.